METODE ELEKTROFOTOKATALISIS DAN FOTOKATALISIS DENGAN TiO2 PADA DEKOLORISASI ZAT WARNA REMAZOL BLACK B DAN PENURUNAN KONSENTRASI ION LOGAM Cu2+ SECARA SIMULTAN - Herlita, Ita; , M.Si., Drs. Gunawan; Haris, M.Si., Drs. Abdul (Chem Info Journal, 2013)
Has done research on use electrophotocataysis and photocatalysis methods by using TiO2 for decolorize of remazol black B dye and decrease the concentration of Cu2+metal ion simultaneously. This research was carried out by electrophotocatalysis is electrolyzing sample solution using and TiO2/FTO as anoda and C as cathoda at a potential of 3 volts and for the photocatalysis was done by the addition of 0.1685 grams of TiO2 powder in the sample solution. The two methods in the photocatalys reactor were irradiation with UV-C light and mixtured using 4 rpm for 210 minutes. Sample solution were analyzed by UV-Vis and AAS. The results showed that electrophotocatalysis more effective methods to decolorize dye solution of remazol black B and to decrease the concentration of Cu2+metal ion simultaneously. Decolorization percentage of remazol black B dye with electrophotocatalysis and photocatalysis methods were 98.65% and 31,05%, while the decrease percentage of Cu2+ metal ion concentration were 98.25% and 31,50% respectively.